2010
DOI: 10.1039/c0cc00824a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and UHV-STM observation of the Td-symmetric Lu metallofullerene: Lu2@C76(Td)

Abstract: The first T(d)-symmetric lutetium metallofullerene, Lu(2)@C(76), has been synthesized, isolated, and characterized. Because of the charge transfer from the encapsulated Lu atoms to the T(d)-C(76) fullerene cage, the otherwise unstable T(d)-C(76) fullerene can be significantly stabilized as a Lu(2)@C(76) fullerene. Both STM and STS results are consistent with a charge state of (Lu(2))(6+)@C(76)(6-)(T(d)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
3
38
1
Order By: Relevance
“…The result is apparently contradicted to the assumption in the experiment [16] that two Lu atoms transfer six electrons to C 76 cage, giving rise to a formal valence state of [Lu 2 ] 6 + @C 76 6À . Furthermore, the HOMO-LUMO gap (1.49 eV) of Lu 2 @C 76 is also close to the gap (1.71 eV) calculated at tetra-anion state.…”
Section: àcontrasting
confidence: 61%
See 2 more Smart Citations
“…The result is apparently contradicted to the assumption in the experiment [16] that two Lu atoms transfer six electrons to C 76 cage, giving rise to a formal valence state of [Lu 2 ] 6 + @C 76 6À . Furthermore, the HOMO-LUMO gap (1.49 eV) of Lu 2 @C 76 is also close to the gap (1.71 eV) calculated at tetra-anion state.…”
Section: àcontrasting
confidence: 61%
“…Herein we present a thorough investigation on a newly isolated dimetallofullerene Lu 2 @C 76 , [16] and find that the two lutetium atoms prefer to bind together to form an unprecedented single metal-metal bond, in a formal valence state of [Lu 2 ] 4 + @C 76 4À by means of combined quantum chemical and statistical thermodynamic approaches. More interestingly, it is shown that the Lu atoms can hop rapidly between six equivalent configurations in the fullerene cage at room temperature, giving rise to a trajectory as a tetrahedron in C 76 (T d ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These features are very similart o those reported for Lu 2 @C 76 ,w hichs uggestsa ni denticalc age structure shared by the two endohedral fullerenes. [32] On the other hand, these absorption features are essentially different from those of DySc 2 N@C s (17490)-C 76 ,w hich indicates am ajor difference in the cage symmetry and the charge transfer between the clusters and outside carbon cages. [47] On the basis of absorption onset at 1587 nm, the optical bandgapo ft his compound was estimated to be 0.79 eV.B yu sing 1.0 eV as the limit to distinguish large-and small-bandgap fullerenes, we can assign this isomer of Sc 2 O@T d (19151)-C 76 as as mall-bandgap fullerene.…”
Section: Sc Nmr Spectroscopymentioning
confidence: 96%
“…[9] Among them,t he T d -C 76 carbon cage, which features the third highest symmetry after I h and I symmetry,h as attracted great interest. [32] Nevertheless,t hough several theoretical and spectroscopics tudies have been devoted to the characterization of T d -C 76 ,b esides af unctionalized C s -(T d -C 76 (CF 3 ) 12 ), [33] Lu 2 @T d -C 76 is the only discovered species so far. [32,[34][35][36] Moreover,t he studies of Lu 2 @T d -C 76 did not provide ad etailed structural analysis because of the lack of unambiguous single-crystal X-ray characterization.…”
Section: Introductionmentioning
confidence: 99%